Ferrovia e organização do espaço urbano em Araguari-MG (1896-1978) - Barbosa, Fábio de Macedo Tristão (2008)
This dissertação looked for to investigate some aspects of the relation of the railroads gifts in Araguari-MG in the organization of the urban space of this city in the period of 1896 the 1978. From a description-geographic approach initially we search to reconstitute gênese and the evolution of the urban space of Araguari, observing the demographic growth and the partner-space development of the city since its first times. We continue, observing the repercussions that had had the expansion of the railroads world measure, its penetration in Brazilian territory e, finally its arrival in Araguari, first, the Company Mogiana de Estrada de Ferro in 1896 e, later the Railroad Goiás in 1906. Araguari is affirmed as important railroad entroncamento swilling down the regional production for the Brazilian Southeast, fact that chose Araguari as regional economic polar region of the Triangle for some time. With the expropriation of the Railroad Goiás for the Federal Government in 1920 which had the constant crises of the capitalism, the Union promoted significant investments in this railroad company, and these resources finish emptying in Araguari that occupied of its administrative headquarters. This fact provided to the adensamento technician- railroad worker in the form-content of the araguarino space, mainly of years 1930 in ahead. The relation railroad-city was gone deep the Brazilian antiliberal capitalism, with the construction of the railroad complex of the Goiás, with laboring village, professional hospital, schools, cooperative of consumption, etc. The Mogiana allowed link with São Paulo for draining of the production, what it also allowed to introduce habits, values, customs, social relations of characteristic production and work of the producing society of merchandises, at last, introduced an urban life railroad worker-capitalist. The city of Araguari, gradual was if configuring as a city- railroad employee and, was this, that this work intended to show